Factors influencing participation of local community in ecotourism development at Bagan Sungai Burung, Bagan Datuk, Perak, Malaysia - Lee, Lin Wei (2020)
This study is aimed to determine the participation level and factors influencing the local community’s participation in sustainable ecotourism development at Bagan Sungai Burung, Perak. Participation of the local community in ecotourism has been highlighted in this study because it is an important input for successful ecotourism development. Lack of specific study on Chinese community and ecotourism participation in Malaysia has created a significant justification as they are the main stakeholders at Bagan Sungai Burung. A quantitative approach was used with a sample size of 200 respondents and multiple regression analysis using stepwise method was employed to identify the significant predictors. Meawhile, the framework of Arnstein’s Ladder of Participation has validated to be useful tool to determine the local community’s participation in ecotourism context. The results showed that low level of citizen power implied that the local authority has included a minimal level of community’s involvement in decision-making process for ecotourism development. Apart from that, the four dimensions of ecotourism impacts had average and strong relationship with each level of ladder of participation. The results showed that perceived economic impact and environmental impact were better determinants for non-participation level. In tokenism level, perceived social impact and economic impact were among the more impactful factors whereas perceived cultural impact and social impact carried stronger predictor in citizen power level. It indicated that the perception of local community on economic, social, cultural and environmental impacts will contribute to willingness of local community’s participation in sustainable ecotourism development. Overall, five independant variables were identified to contribute significantly in clarifying the overall level of participation in ecotourism development which included occupation, duration of ecotourism engagement, number of family member’s involvement in ecotourism, perception of local community towards homestay programme and perceived cultural impact. Since the moderate participation level of local community in ecotourism development, local authorities such as Perak State Parks Corporation should increase the development of various ecotourism activities and facilities to sustain the active involvement of local community in ecotourism operation. Training and assistance related to ecotourism for local community should be provided in order to motivate them to participate in meetings and actively express their opinions and views. Therefore, local government should include community participation in planning, management and decision-making process. With cooperation of local community and local authorities, a balance development can be achieved to maintain the increasing number of tourists and at the same time giving benefits continuously and ensure the well-being of local community.